An examination of linkages between CSR and cross-buying. Issue 3 (3rd August 2015) - Vyas, Vishal; Raitani, Sonika
Abstract : Purpose: – This paper aims to probe into the linkages between the corporate social responsibility (CSR) practices of banks and the cross-buying intentions of banking customers. Though the authors could not find any direct link between these two concepts on theoretical ground, but an effort has been made to identify the impact of CSR on cross-buying intentions through corporate reputation and relationship quality. Like other industries, the Indian banking industry has also witnessed a balance between its social-environmental responsibilities and its clearly defined economic responsibility to earn profit. Design/methodology/approach: – The universe for the present study constitutes the customers of the entire Indian banking industry. Considering the cost and time constraints, the study was limited to a sample of 347 public and private bank customers in the Rajasthan region based on the convenience sampling method. Data were collected using a structured questionnaire and analyzed through structural equation modeling. CSR measures included philanthropic and ethical responsibility. Findings: – Results revealed that corporate reputation and relationship quality both play a mediating role in the linkages between CSR and cross-buying intentions. Practical implications: – The study suggests integrating marketing strategy with its CSR strategies to encourage cross-buying intentions. While making the cross-selling agenda, they should bear reputation in mind because at the relationship development phase, customers generally rely on reputation than their evaluation of bank's products for cross-buying. Originality/value: – This study is the first in marketing literature which relates the concept of CSR and the cross-buying.